Conversation between a Sociologist and a Lawyer about the Latent Crime and not only about it… - Rushchenko, Ihor (2003)
The article is written in form of pseudo dialogue between sociologist and lawyer. The data of interrogation of Kharkiv region in habitants in few indicators is showed in the article: 1. A part of victimized residents during last 12 months (population’s victimization proportion). 2. General quantity of reported crimes during survey. 3. Quantity of police reports. 4. Degree of latency. The so called “Latency paradox” as a world-view and as a methodological problem is discussed in the article. The author maintains the thought about necessity of developing the domestic sociology of crime in cooperation with other criminal-law disciplines.